1995
DOI: 10.1002/mrc.1260330806
|View full text |Cite
|
Sign up to set email alerts
|

1H and 13C NMR spectra of the methanolic allomerization products of 132(R)‐chlorophyll a

Abstract: The spontaneous autoxidation (allomerization) of 13'(R)-chlorophyll u in methanol produces seven main products containing three epimer pairs. The 'H and ' ' C NMR spectra of these products in acetone-d, were recorded on a 500 MHz spectrometer and fully assigned using two-dimensional HMQC and HMBC techniques. The absolute configurations of the oxidized carbons, originally C-13', were determined using the ROESY technique. In comparison with 13'(R)-chlorophyll u, the steric repulsion between the C-17 side-chain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 28 publications
3
27
0
Order By: Relevance
“…The ease of loss of the C‐13 2 substituent as water from the S diastereomer was attributed to greater steric strain in the C‐13 2 carbonoxygen bond, resulting from steric repulsion between the substituent and the C‐17 propionate ester substituent on the same plane of the macrocyclic ring. NMR studies have confirmed epimer I as S configuration and epimer II as R configuration 6…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The ease of loss of the C‐13 2 substituent as water from the S diastereomer was attributed to greater steric strain in the C‐13 2 carbonoxygen bond, resulting from steric repulsion between the substituent and the C‐17 propionate ester substituent on the same plane of the macrocyclic ring. NMR studies have confirmed epimer I as S configuration and epimer II as R configuration 6…”
Section: Resultsmentioning
confidence: 93%
“…2 15 1 ‐MeO‐lact‐chl a , 13 2 ‐MeO‐chl a 2,3 and 13 2 ‐HO‐chl a 3–5 exist as two diastereomers differing at position C‐13 2 or C‐15 1 . Recently, full spectral assignment including the designation of the stereochemical configurations of three pairs of diastereomers has been achieved by complete assignment of the 1 H and 13 C nuclear magnetic resonance (NMR) and 2D ROESY spectra 6. Structural elucidation by NMR is rigorous but time‐consuming and often requires milligram quantities of highly purified sample.…”
mentioning
confidence: 99%
“…NH tautomerism) remained undetermined. Nowadays, the utilization of high-field NMR instruments and advanced NMR techniques offers an efficient way to obtain detailed solution structures for substituted chlorins [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…oxidative degradation reactions involving oxidations, hydroxylation, ring-opening or decarboxylations of the isocyclic pentanone ring. The most comprehensive treatise on Chl chemistry remains the article by Hynninen (1991). Only a few developments have been made in the last decade, which will be the focus of this review.…”
Section: Basic Structure and Reactivity Of Chlorophyllsmentioning
confidence: 99%
“…Several analytical studies, mostly employing modern mass spectrometric methods, were aimed at studying the allomerization reaction of Chl (Grese et al, 1990;Rahmani et al, 1993;Brereton et al, 1994;Hyvarinen et al, 1995). A thorough study by Woolley et al (1998) clearly showed that the 13 2 -CO 2 Me group is required for allomerization Scheme 4 to occur and that a double rather than single bond between C7 and C8 (e.g., Chl vs. BChl) exerts a significant influence on the reactivity of ring E: ring E in Chl a is more susceptible to oxidative ring cleavage and lactone formation than in BChl a.…”
Section: Chemical Manipulations Of Ring Ementioning
confidence: 99%